Aktivitas Antibakteri Ekstrak Isolat Jamur Endofit Aspergillus sp. yang Berasosiasi dengan Mangrove Rhizhopora apiculata terhadap Patogen Ikan Laut - Dharmawati, Verli; Susanto, G. Nugroho; Nurcahyani, Nuning; Damai, Abdullah Aman; Azzuhdy, Afifah Nissa (Journal of Tropical Marine Science, 2024)
Exploration of microorganisms containing secondary metabolite compounds with antimicrobial properties, especially in marine fish pathogenic bacteria, is urgently required. This study aims to test the antibacterial effectiveness of endophytic fungal extracts from the mangrove plant Rhizopora apiculata in the Petengoran Mangrove Forest against pathogenic bacteria in marine fish such as V. alginolyticus and P. damselae spp. The endophytic fungal isolate found was a fungus from the genus Aspergillus sp after observing its morphological form macroscopically and microscopically. Ethyl acetate extract of mangrove endophytic fungi with a concentration of 500 µg/disc and 1000 µg/disc was dripped onto a 6mm paper disc and then placed on the pathogenic bacterial isolate. Measurement of the diameter of the clear zone produced around the paper disc after 24 hours concluded that the antibacterial effectiveness of the endophytic fungal extract against V. alginolyticus was 27.27% (500 µg/disc) and 32.32% (1000 µg/disc). Meanwhile, its effectiveness against P. damselae spp is 27.27% (500 µg/disc) and 34.82% (1000 µg/disc). The isolate extract from the endophytic fungus Aspergillus in this study has the potential to produce antibacterial compounds in marine fish pathogens.